Structural, magnetic and hyperfine characterization of ZnxFe3–xO4 nanoparticles prepared by sol-gel approach via inorganic precursors. (March 2018) - Kotsikau, Dzmitry; Pankov, Vladimir; Petrova, Elena; Natarov, Valentin; Filimonov, Dmitry; Pokholok, Konstantin
Abstract: Structural characteristics and magnetic properties of Zn x Fe3– x O4 (where х  = 0; 0.09; 0.18; 0.45; 1) nanoparticles were studied with X-ray diffraction (XRD), transmission electron microscopy (TEM), infrared spectroscopy (IR) and vibrating sample magnetometry (VSM). Oxidation of Fe 2+ ions, redistribution of Zn 2+ and Fe 3+ ions between octahedral and tetrahedral sites, and the formation of cation vacancies in spinel-type cubic structure of the obtained Zn x Fe3– x – y □ y O4 substitutional solid solutions were revealed by 57 Fe Mössbauer spectroscopy. The nanoparticles synthesized via a modified sol-gel method using inorganic precursors have a size of 4–10 nm, single-phase composition, superparamagnetic behavior at room temperature (300 K) and a relatively hydrophilic surface to form stable aqueous suspensions. The maximum magnetization of 59 emu/g at 300 K corresponds to Zn0 . 18 Fe2 . 82 O4 composition. The listed features make the materials promising candidates for various biological and medical applications such as contrast-enhanced magnetic resonance imaging, hyperthermia of pathological tissues, controlled drug release, and separation of nucleic acids. Highlights: Structural features and magnetic properties of Zn-doped magnetite were characterized. A facile modification of sol-gel method was used to obtain Zn x Fe3– x O4 nanoparticles via inorganic precursors. Iron and zinc ions redistribution and cation vacancies formation under doping magnetite with zinc were studied by Mössbauer spectroscopy. Synthesized Zn x Fe3– x O4 nanoparticles are promising material for biomedical applications.